Gambaran Fraksi Hemoglobin Penderita Talasemia Menggunakan Metode Elektroforesis Kapiler - Suryanata Kesuma; Elita Octavia (Jurusan Analisis Kesehatan, Poltekkes Kemenkes Denpasar, 2018)
Thalassemia is a hereditary blood disease that is found in Indonesia. One method of examining modern thalassemia is the examination of hemoglobin fraction using the Capillary Electrophoresis. This method has a high level of accuracy and precision for quantification of hemoglobin variants.The purpose of this study was to determine the hemoglobin fraction in thalassemia patients using the Capillary Electrophoresis method. This type of research is descriptive research. The sample of this study was 3 blood specimens from thalassemia sufferers.The results showed that the first specimen, age 4 years had HbA levels of 59.9%, HbA2 levels of 4.3%, HbF levels of 14.7% and HbE levels of 21.1%. In the second specimen, 8 years of age had 88.7% HbA, 2.5% HbA2, 3.2% HbF and 5.6% HbE. In the third specimen, the age of 13 years had HbA levels of 93.8%, HbA2 levels of 4.9% and HbF levels of 1.3%.The conclusion of this study was the first specimen, HbA levels decreased, HbA2 levels increased and HbF levels increased and hemoglobin variants were found, namely HbE. In the second specimen, HbA levels decreased from the normal range, HbA2 levels were in the normal range and HbF levels increased and hemoglobin variants were found, namely HbE. In the third specimen, HbA levels decreased from the normal range, HbA2 levels and HbF levels increased, but no hemoglobin variants were found in this specimen.